Some Variable Traits of Broiler Genotypes - Holcvart, Mária (Acta Agraria Debreceniensis, 2020)
One the most effective ways to satisfy the requirements of mankind for food of animal origin is the fattening of chicken. Healthy and cheap meat with low fat and high protein content can be produced rapidly and in large quantities by broilers with low feed consumption. This paper presents the production results and carcass traits of three genotypes (Ross 308, Cobb 500, Ross broiler parent) females and males at the age of 42 days. In both sexes, we found that the average body weight of the Ross parents genotype was higher (females: 2643 g; males: 3089 g) than the average body weight of the other two hybrids – significant difference was found only between pullets. However, the smallest difference in the average body weight between the two sexes (446 g) was found in this genotype. In both sexes, the lowest average weight was detectable in the case of the Cobb 500 hybrids (females: 2443 g; males: 3052 g).The feed consumption ability of the females were worse – in all but one case (Ross pullet) – than that of the males. For one kg of weight gain - in the order of genotypes – 1.79kg, 2.08kg and 2.08 kg of feed was used. The same values for the males were as follows: 1.81kg, 1.80kg and 1.89 kg, respectively. Carcass traits were examined and it was found that the average grillfertig weight, the weight of whole thigh meat and thigh meat of the Ross parents’ genotype was higher than the average weight of the other two hybrids. Significant difference was found only in grillfertig- and whole thigh meat weight. Pullets of the Ross parents’ paternal line had worse results in the average weight of breast meat with bone and breast meat fillet than the other two genotypes. In the case of cocks was detectable the inverse of this: the average weight of breast meat with bone was the highest in the cocks of the Ross parents’ maternal line.